2015
DOI: 10.1016/j.ejvs.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Aneurysm Repair of Aortoiliac Aneurysms with an Iliac Side-branched Stent graft: Studying the Morphological Applicability of the Cook Device

Abstract: In the present cohort with aorto-iliac aneurysm, a maximum of 58% could have been treated with an iliac side branch based on the current experience. In particular, an aneurysmal IIA seems to be a limiting factor for the use of the iliac side-branched stent graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 20 publications
4
36
1
Order By: Relevance
“…However, institutions and operators have successfully deployed these devices outside of the IFU according to institutional protocol. 35 As overall inclusion percentages were similar in this Japanese study compared to global studies, this supports multi-national clinical trials to evaluate new stent design, such as was done for drug eluting technology in peripheral arterial disease patients. 41 …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, institutions and operators have successfully deployed these devices outside of the IFU according to institutional protocol. 35 As overall inclusion percentages were similar in this Japanese study compared to global studies, this supports multi-national clinical trials to evaluate new stent design, such as was done for drug eluting technology in peripheral arterial disease patients. 41 …”
Section: Discussionsupporting
confidence: 74%
“…The Cook IBD incorporates a branch limb off an iliac limb requiring a longer CIA segment and larger EIA diameter; whereas the IBE uses a short, narrow EVAR device to deploy above the iliac bifurcation thereby requiring a proximal CIA diameter > 17 mm and an aorto-iliac length to be > 165 mm. Our series showed similar percentages for inclusion for the Cook IBD (18–33%) and Gore IBE (23%) 18,35,40 . However, institutions and operators have successfully deployed these devices outside of the IFU according to institutional protocol.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In a study from 2010 it was pointed out that the morphological applicability of commercially available ISBD was low [29]. A recent study by Gray et al showed that only a maximum of 58 % of the patients in their cohort were within the manufacturer's IFU with the main limiting factor of an aneurysmal hypogastric artery that prevent adequate distal sealing [30]. In an adverse morphological situation, extending the landing zone more distally in the hypogastric artery is possible, but the risk of a worse result by sacrificing smaller branches with an increased risk of endoleak type II is given [30].…”
mentioning
confidence: 99%
“…A recent study by Gray et al showed that only a maximum of 58 % of the patients in their cohort were within the manufacturer's IFU with the main limiting factor of an aneurysmal hypogastric artery that prevent adequate distal sealing [30]. In an adverse morphological situation, extending the landing zone more distally in the hypogastric artery is possible, but the risk of a worse result by sacrificing smaller branches with an increased risk of endoleak type II is given [30]. Furthermore, the risk of endoleak type Ib could be higher when choosing a shorter landing zone in the more distal branches of hypogastric artery.…”
mentioning
confidence: 99%